Detection of toxigenic mycobiota and mycotoxins in cereal feed market. (February 2018) - Hassan, Zahoor Ul; Al-Thani, Roda Fahad; Migheli, Quirico; Jaoua, Samir
Abstract: The present study was designed to investigate the occurrence of mycotoxins and toxigenic mycobiota in cereals used as animal feed in a Qatari market. Aflatoxins (AFs) and ochratoxin A (OTA) were detected in 94 and 44% of mixed cereals, 70 and 40% of maize, 40 and 60% of wheat and wheat bran samples, respectively. Among these positive samples, 20 and 14% (of mixed cereals), 29 and 50% (of maize) were found to be contaminated with levels higher than the European Union (EU) permissible limits for AFs and OTA, respectively. The co-contamination analysis showed that 44, 40 and 50% of the mixed cereals, maize and barley samples were concurrently contaminated with AFs and OTA. In all the tested samples, Aspergillus was the most predominant genus with isolation frequency ranging from 67 to 100%. Likewise, the relative density (occurrence compared to the other genera) of Aspergillus was 42–71% in the different cereals samples. Mixed cereals showed the maximum fungal load with 3 × 10 3 colony forming units/g. Based on species-specific PCR primers, among Aspergillus species, A. flavus, A. parasiticus A. niger, A. carbonarius, A. ochraceus and A. westerdijkiae were the most predominant. Most of the isolates presented the key genes for either the aflatoxigenic ( omt-1, ver-1 and apa-2 ) or ochratoxigenic ( pks ) biosynthesis pathways. In spite of possessing mycotoxigenic genes, 10, 20, 17 and 50% of A. flavus, A. parasiticus, A. carbonarius and A. niger isolates, respectively, did not produce any AFs or OTA in culture media. Our findings demonstrate that cereals used as animal feeds are generally contaminated with variable levels of mycotoxigenic fungi and mycotoxins, with maximum levels being present in mixed cereals and maize samples. Highlights: Mycotoxigenic fungi and mycotoxins are present in the cereal marketed in Qatar. Significant number of samples have mycotoxins levels above EU permissible limit. PCR based identification of toxigenic fungi ensures sufficient specificity. There is no diversity in pks gene of A. ochraceus and A. westerdijkiae. 50% of the A. niger isolates, in spite of having toxigenic gene, didn't produced OTA.